A material model for lamination stacks based on rough contacts - Luchscheider, Vera; Willner, Kai; Maidorn, Mischa (2014 4th International Electric Drives Production Conference, EDPC 2014, 2014)
This contribution presents, how to identify a material model of a lamination stack. The contact behavior between the single sheets is nonlinear and influences the behavior of the whole stack. The Simulation of the contact behavior is performed with contact models for normal and tangential direction. Due to the fact that calculating all sheets with contact is computational very expensive, a FE2-method is presented. With this method the calculation of the stack's behavior is based on a representative volume element. Further it is possible to identify a material model for the whole stack, which has got a linear and a nonlinear part. The linear part is caused by the material of the sheet, whereas the nonlinear part is a result of the contact behavior.
Keywords: lamination stack; material model; multiscale homogenization; normal and tangential contact behavior